Islamic Finance Integration in the Halal Wagyu Global Value Chain: Sharia-Compliant Instruments, Governance, and Policy Implications - Prima Gandhi; Triyanto Triyanto (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
The global halal food market has evolved from a niche religious segment into a mainstream component of international agrifood trade, driven by demographic growth, rising middle-class incomes, and greater awareness of halal standards. Within this context, Japan occupies a distinctive position as a non-Muslim, high-income country with an advanced agrifood sector and strong branding around safety, quality, and traceability. Wagyu beef has become a flagship export, and the emergence of halal-certified wagyu has opened a high-value but still niche channel linking Japanese producers to Muslim markets in Southeast Asia and the Middle East, while facing governance and financing challenges such as fragmented certification, midstream bottlenecks, and limited Islamic finance integration. This article examines how halal-certified Japanese wagyu participates in global halal agrifood trade and how Islamic finance can support its development. Using qualitative document analysis of academic, policy, industry, and media sources, it maps the halal wagyu global value chain from upstream breeding and fattening in Japan to midstream slaughtering and processing, and downstream logistics, export, and retail in Muslim-majority markets. The findings show that halal governance relies on layered assurance across slaughter, processing, packaging, logistics, and food service, anchored in Japan’s beef traceability system and private halal certification and logistics standards. The study demonstrates that halal wagyu occupies a high-margin niche driven by affluent Muslim consumers but constrained by limited certified processing capacity, high compliance and logistics costs, and fragmented recognition of certifiers and regulations.